2018
DOI: 10.1088/1741-4326/aad70c
|View full text |Cite
|
Sign up to set email alerts
|

Observation of toroidal Alfvén eigenmode excited by energetic electrons induced by static magnetic perturbations in the EAST tokamak

Abstract: A toroidal Alfvén eigenmode (TAE) excited by barely trapped energetic electrons during the application of a static magnetic perturbations (MPs) is observed for the first time in tokamak ohmic heating plasmas. This TAE appears when the current of a static n  =  2 MPs exceeds a threshold value, at which a forced n  =  2 magnetic reconnection happens. Here, n is the toroidal mode number. This TAE is located near the plasma edge, which agrees with the calculation of the TAE gap. It propagates in the ion diamagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
0
26
0
3
Order By: Relevance
“…In EAST LHW experiment [26], the observed AEs can propagate in either ion or electron diamagnetic drift direction. In addition, it was recently reported that energetic electrons induced by static magnetic perturbations can also drive a TAE propagating in the ion diamagnetic drift direction [27]. These experimental studies revealed some properties of energetic-electron driven AE, including its frequency, mode number and propagation direction.…”
Section: Introductionmentioning
confidence: 89%
“…In EAST LHW experiment [26], the observed AEs can propagate in either ion or electron diamagnetic drift direction. In addition, it was recently reported that energetic electrons induced by static magnetic perturbations can also drive a TAE propagating in the ion diamagnetic drift direction [27]. These experimental studies revealed some properties of energetic-electron driven AE, including its frequency, mode number and propagation direction.…”
Section: Introductionmentioning
confidence: 89%
“…This provides an approximate boundary between instabilities that act on REs in real space (< 30 MHz) and those that act on REs in phase space (> 30 MHz). Consequently both few MHz instabilities, 10-100s kHz MHD instabilities, and stationary applied 3-D fields can deconfine REs in effectively the same manner [42,8,82,70,43,16,41].…”
Section: General Prospects For Kinetic Instabilitiesmentioning
confidence: 99%
“…(Experimental Advanced Superconducting Tokamak)上 观测到环效应引起的阿尔芬本征模(Toroidicity-Induced Alfvén Eigenmodes, TAEs) [10,11] 、比压阿尔芬本 征模(Beta-Induced Alfvén Eigenmodes, BAEs) [12,13] 以及 反磁剪切阿尔芬本征模(Reverse Shear Alfvén Eigenmodes, RSAEs) [14,15] 等. 这些模式在不同装置的不同放 电条件下呈现出不同特性, 如在HL-2A上高能离子激 发的BAE具有频率啁啾特性 [16] , 而在EAST上BAE的 存在依赖于低杂波功率, 并且磁重联对其有很大影响 等 [11] .…”
Section: 引言unclassified